ARTIFICIAL INTELLIGENCE TECHNOLOGY AS A TREND IN THE UTILIZATION OF ENGLISH LANGUAGE LEARNING - Ridayani Ridayani (CV. Adiba Aisha Amira, 2024)
The use of AI in language learning and shows the great potential of AI in the development of innovative and Creative learning methods. The purpose of this study is to determine the role of AI Technology as a trend in the utilization of English language learning. This research method is qualitative with descriptive analysis, namely the data used by skunder data, which is in the form of books and research research related to AI Technology as a Trend in the Utilization of English Language Learning and in this study seeks to focus on AI Technology Analysis as a Trend in the Utilization of English Language Learning. And this type of research is library research or literature review. Data collection techniques classify discourses, journals, articles, books and journals related to the title of the study, the results of this study are.